Interventional therapy for brain arteriovenous malformations before and after ARUBA. (March 2017) - Sussman, Eric S.; Iyer, Aditya K.; Teo, Mario; Pendharkar, Arjun V.; Ho, Allen L.; Steinberg, Gary K.
Highlights: ARUBA concluded that medical management alone is optimal for unruptured bAVMs. The volume and treatment strategy of bAVMs at Stanford has not changed significantly. The long-term impact of the ARUBA on management of bAVMs is yet to be determined. Abstract: The ARUBA trial (2014) concluded that medical management alone is superior to medical management plus interventional therapy for the treatment of unruptured brain arteriovenous malformations (bAVMs). This sparked considerable controversy among involved healthcare providers. Here, we evaluated the impact of ARUBA on the volume, type, and treatment modality of bAVMs referred to a large tertiary care center. This was achieved by conducting a retrospective review of a prospectively maintained database of all bAVMs treated at Stanford Health Care and Stanford Children's Health from January 2012 through July 2015. The case volume of bAVMs treated at Stanford has been relatively unchanged in the period of time leading up to and after ARUBA. Furthermore, there has been no significant change in the proportion of unruptured AVMs treated. Although differences existed in types of interventions administered, these differences are best explained by variations in the SM grades of AVMs treated during each study period, rather than by underlying changes in treatment strategy. Additional research is warranted to more thoroughly characterize the impact of ARUBA on the treatment patterns of bAVMS.